1999
DOI: 10.2307/1369990
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Abundance, and Habitat Characteristics of the Buff-Breasted Flycatcher in Arizona

Abstract: INFORMATION TO USERSThis manuscript has been reproduced from the microfilm master. UMI films the text directfy fix>m the originai or copy submitted. Thus, some thesis and dissertation copies are in ^ewiiter &ce; vt^e others may be fi'om aiQr Qrpe of computer printer.The quality of this reprodnctioii is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…Foraging habitats are thought to improve with clearing of the understory such as by low severity fires (Martin and Morrison 1999). Other studies have suggested that more intense fires are needed to provide sustainable habitats .…”
Section: Management Implicationsmentioning
confidence: 99%
“…Foraging habitats are thought to improve with clearing of the understory such as by low severity fires (Martin and Morrison 1999). Other studies have suggested that more intense fires are needed to provide sustainable habitats .…”
Section: Management Implicationsmentioning
confidence: 99%
“…Environmental disturbances such as caused by fire often modifies a habitat from its preimpact form (Turner et al, 2003); some of the detectable changes induced by fires include reduction in foraging habitat (Bowers et al, 1996;Martin and Morrison, 1999), reduction in vegetation cover such as seedlings, saplings, canopy, large trees (Smucker et al, 2005) and litter cover (Kutt and Woinarski, 2007) as well as reduction in species densities (Nelson et al, 2008). Such effects often produce a new set of challenges on survival and reproduction for organisms occupying such habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Historical records in central Arizona and central New Mexico were not rare and evidence of breeding was repeatedly noted in appropriate habitat throughout the region (Bendire 1892, Bailey 1928, Bent 1942, Ligon 1961, Phillips et al 1964). However, distribution and numbers of buff-breasted flycatchers declined between the late 1800s and 1970 (Phillips et al 1964, Bowers and Dunning 1994, Martin and Morrison 1999. Indeed, Phillips et al (1964:86) stated that buffbreasted flycatchers had ''decreased markedly'' in Arizona between 1920 and 1964, and buff-breasted flycatchers were formerly a Category 2 species under the Endangered Species Act (Federal Register 1994, 1996.…”
mentioning
confidence: 99%
“…Currently, buff-breasted flycatchers are very rare in the United States (Arizona Fish Department 1995, Conway andKirkpatrick 2001) and are known to breed only in several locations in extreme southeastern Arizona (primarily in the Huachuca and Chiricahua Mountains). The known United States breeding population consisted of 131 individuals in 1995-1996 (Martin 1997) and population status and trends in Mexico are not known. Range contraction and the small number of breeding pairs in the United States have caused concern among government agencies and conservation organizations (Arizona Fish Department 1988, 1996;Hunter et al 1993;Bowers and Dunning 1994;Latta et al 1999).…”
mentioning
confidence: 99%